Metacognitive Strategies and Willingness to Communicate in L2 Learning: A Mediation Model of Self-Efficacy and Intrinsic Motivation - Mao Zhao; Ting Li; Yating Yu; Kuen Fung Sin; En Zheng (SAGE Open)
In the sphere of second or foreign language (L2) pedagogy, empirical evidence has increasingly spotlighted the role of learners’ metacognitive strategies as formidable predictors of their willingness to engage in L2 communication (WTC). Nonetheless, the interrelationship among learners’ metacognitive strategies, self-efficacy, and intrinsic motivation—as a collective force influencing WTC—has not been adequately probed. Addressing this gap, the present research determines the mediating roles of L2 self-efficacy and intrinsic motivation in bridging metacognitive strategies with WTC. The research cohort consisted of undergraduates majoring in English at leading national universities in China, with a comprehensive survey conducted among 316 respondents. The analysis unveiled two pivotal findings: (1) there exists a significant predictive relationship between students’ metacognitive strategies and their WTC in L2, and (2) students’ self-efficacy and intrinsic motivation in the L2 context mediate this relationship. This study emphasizes the importance of metacognitive strategies, self-efficacy, and intrinsic motivation in promoting L2 communication. The significance and directions for future studies are also discussed.